2020
DOI: 10.3390/math8030441
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Correlations and Characterization of Financial and Volcanic Time Series

Abstract: In this study, we use the Diffusion Entropy Analysis (DEA) to analyze and detect the scaling properties of time series from both emerging and well established markets as well as volcanic eruptions recorded by a seismic station, both financial and volcanic time series data have high frequencies. The objective is to determine whether they follow a Gaussian or Lévy distribution, as well as establish the existence of long-range correlations in these time series. The results obtained from the DEA technique are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…is is aimed at analysing exchange rate markets from the time-frequency domain perspective instead of the traditional time-domain viewpoint. e Fourier and wavelet transform approaches of studying the time-frequency domain have been widely used in this regard [17][18][19]. Huang et al [20] noted that Fourier-based approaches are not data-adaptive, unable to capture the timevarying characteristics of the neural signal, and only designed for the frequency analysis of stationary time series.…”
Section: Introductionmentioning
confidence: 99%
“…is is aimed at analysing exchange rate markets from the time-frequency domain perspective instead of the traditional time-domain viewpoint. e Fourier and wavelet transform approaches of studying the time-frequency domain have been widely used in this regard [17][18][19]. Huang et al [20] noted that Fourier-based approaches are not data-adaptive, unable to capture the timevarying characteristics of the neural signal, and only designed for the frequency analysis of stationary time series.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, we have a quadratic log-log dependence, of which the linear log-log dependence (3) is a particular case corresponding to b 1 = 0. Such dependencies is really ubiquitous: e.g., an empirical analysis provided in [2] have shown that many real-life dependencies, ranging from economic to volcanic data, follow these formulas. This naturally leads to the following questions.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…If a fractal object is successively magnified, it looks similar or exactly like the original shape of the fractal. A similar pattern exhibited at increasingly smaller scales is often known in fractal mathematics as self-similarity [2,3]. In time series, self-similar phenomena describe the event in which the dependence in the time series decays more slowly than an exponential decay.…”
Section: Introductionmentioning
confidence: 97%
“…In [11], a clear comparison was made between DNA and economics by the authors, showing the underlining similarities that allow researchers to model seemingly different phenomena using the same or slightly modified models. In the same manner, these variance scaling models have the added advantage of being used to model long memory effects in different fields where stochastic processes occur [2,7]. Thus, be it DNA sequencing, financial markets, geophysical time series etc., scaling methods have been used to detect long/short memory behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation